Severe Intellectual Disability: Systematic Review of the Prevalence and Nature of Presentation of Unipolar Depression. Issue 5 (22nd June 2015) - Walton, Catherine; Kerr, Mike
Abstract : Background: The diagnosis of depression in severe and profound intellectual disability is challenging. Without adequate skills in verbal self‐expression, standardized diagnostic criteria cannot be used with confidence. The purpose of this systematic review was to investigate the assessment and diagnosis of unipolar depression in severe and profound intellectual disability. The review aimed to examine the methods used to assess for depression. The secondary aim was to explore the frequency and symptoms of depression. Methods: The PRISMA (2009) Checklist for systematic review was followed, and a search of electronic databases was undertaken. Nine studies were included in the qualitative synthesis from over 2000 records identified. Results: The quality of the studies was assessed and scored, with a wide range of results. Individual studies scored between 2 and 7 of a maximum possible score of 8. The diagnostic tools utilized by each of the studies were assessed and compared. Conclusions: In terms of the methods used to assess for depression, results were varied. This was due to the heterogeneous nature of the individual study designs. The Aberrant Behaviour Checklist consistently showed promise, in particular when combined with other instruments or clinical examination. Qualitative analysis of the selected studies has shown a wide variation in the quality of primary research in this field, with more required to make firm conclusions regarding the diagnosis, frequency and presentation of depression in severe and profound intellectual disability.